A cost-effectiveness assessment of dual-mobility bearings in revision hip arthroplasty. (14th September 2020) - Khoshbin, Amir; Haddad, Fares S.; Ward, Sarah; O hEireamhoin, S.; Wu, James; Nherera, Leo; Atrey, Amit
Abstract : Aims: The rate of dislocation when traditional single bearing implants are used in revision total hip arthroplasty (THA) has been reported to be between 8% and 10%. The use of dual mobility bearings can reduce this risk to between 0.5% and 2%. Dual mobility bearings are more expensive, and it is not clear if the additional clinical benefits constitute value for money for the payers. We aimed to estimate the cost-effectiveness of dual mobility compared with single bearings for patients undergoing revision THA. Methods: We developed a Markov model to estimate the expected cost and benefits of dual mobility compared with single bearing implants in patients undergoing revision THA. The rates of revision and further revision were calculated from the National Joint Registry of England and Wales, while rates of transition from one health state to another were estimated from the literature, and the data were stratified by sex and age. Implant and healthcare costs were estimated from local procurement prices and national tariffs. Quality-adjusted life-years (QALYs) were calculated using published utility estimates for patients undergoing THA. Results: At a minimum five-year follow-up, the use of dual mobility was cost-effective with an estimated incremental cost-effectiveness ratio (ICER) of between £3, 006 and £18, 745/QALY for patients aged < 55 years and between 64 and 75 years, respectively. For those aged > 75 years dual mobility was only cost-effective if the timeline was beyond seven years. The use of dual mobility bearings was cost-saving for patients aged < 75 years and cost-effective for those aged > 75 years if the time horizon was beyond ten years. Conclusion: The use of dual mobility bearings is cost-effective compared with single bearings in patients undergoing revision THA. The younger the patient is, the more likely it is that a dual mobility bearing can be more cost-effective and even cost-saving. The results are affected by the time horizon and cost of bearings for those aged > 75 years. For patients aged > 75 years, the surgeon must decide whether the use of a dual mobility bearing is a viable economic and clinical option. Cite this article: Bone Joint J 2020;102-B(9):1128–1135.